VD_FINDINFO Décision / 2017 / 776 vom 3. Oktober 2017 - VD Tribunal cantonal (2017)
ORDONNANCE PÉNALE, FICTION DE LA NOTIFICATION, DOMICILE ÉLU | 353 CPP (CH), 355 CPP (CH), 356 CPP (CH), 85 CPP (CH), 87 CPP (CH)